KOMUNIKASI PERSUASIF PADA PROGRAM ACARA PENDIDIKAN “YO NGOPI LUK” TVRI BANGKA BELITUNG - Pebri Yanasari (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
One method that can be used by communicators to give influence and effect to the communicant is to use persuasive communication. In this study, researchers analyzed the educational program